Aplicación móvil para el control del mantenimiento de los vehículos que ingresan al taller mecánico integral GAB Motors - Chasiluisa Chicaiza, Marco Vinicio (2017)
This project of investigation was made with the purpose to contribute to the improvement of communication between the administrator of the integral workshop Gab Motors and its customers by means the creation of a mobile application for the platform Android, same that was developed through the use of Mobile-D methodology designed for the development of mobile applications, ideal for the work in small teams working in group to supply a product of software in short terms. This application allows to the customer manage information of his vehicles, profile, reservation of appointments obtaining like answer notifications to the mobile device for the next checkup, as well as also the visualisation of the maintenances made by means of the consumption of a web service. Besides, it opted for developing an application of web administration in which the administrator of the workshop has the possibility to manage customers, vehicles, register the maintenances also the attention of the daily appointments reserved by the customers. The project has like purpose improve the process of management of vehicular maintenances generating a correct communication between the administration of the workshop and his customers achieving of this way increase the quality of the service with both parts of the necessary information that contribute with the decisions at the moment to diagnose or repair the vehicles.